1991
DOI: 10.1111/j.1365-246x.1991.tb04610.x
|View full text |Cite
|
Sign up to set email alerts
|

On ISCPPandpPdata and their use in delay-time tomography of the Caribbean region

Abstract: 169A shortcoming of t h e resolution tests used in our study is that some specific problems of reported delay times are not reflected in synthetic data. We observe that ISC delay times of later arriving phases are not necessarily consistent with the reported hypocentral parameters, as most ISC-reported earthquake locations are computed from direct P-wave data. For t h e pP data, t h e inconsistency with event location not only results in a decrease of focal depths during relocation, but in a bias of the imaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…These phases, especially bouncing multiple times off large unobstructed oceans, can provide unique ray wave path sampling locations. To date, many global tomographic studies have straightforwardly shown that the combination of later arrivals can offer a substantial increase in the resolution of fine‐scale velocity mapping (Amaru, 2007; Fukao et al., 2003; Hosseini et al., 2019; Li et al., 2008; Obayashi et al., 2013; Van der Hilst & Engdahl, 1991; Vasco & Johnson, 1998). However, because most teleseismic ray paths are near vertical ray incidents at shallow depths, this leads to vertical smearing.…”
Section: Introductionmentioning
confidence: 99%
“…These phases, especially bouncing multiple times off large unobstructed oceans, can provide unique ray wave path sampling locations. To date, many global tomographic studies have straightforwardly shown that the combination of later arrivals can offer a substantial increase in the resolution of fine‐scale velocity mapping (Amaru, 2007; Fukao et al., 2003; Hosseini et al., 2019; Li et al., 2008; Obayashi et al., 2013; Van der Hilst & Engdahl, 1991; Vasco & Johnson, 1998). However, because most teleseismic ray paths are near vertical ray incidents at shallow depths, this leads to vertical smearing.…”
Section: Introductionmentioning
confidence: 99%